(untitled) (Revista Científica Ciencias Naturales y Ambientales, 2022)
Greenhouse gas (GHG) emissions are a latent concern for all countries in the world, for this reason, many of the countries are part of the creation of treaties, agreements and regulations that allow raising awareness and setting goals for the common good. The estimations of the determining factors directed to CO2 emissions, is evidenced by means of the logarithmic mean decomposition (LMDI) that allows to know the variation of these emissions. The aforementioned method presents great robustness for the estimation of this type of analysis, the decomposition of the factors of energy mix (Mix), carbonization index (Ic), energy intensity (Ie), economic activity (Act) and population (P) applied to two of the most representative sectors of Ecuador (Transport and Industrial) in terms of energy consumption, shows that between 2000 - 2020 emissions in the transport sector have increased 5,56 Mt of CO2, while in the industrial sector emissions show a reduction of 1,83 Mt of CO2. The study carried out shows that the determining factors in the transport and industrial sectors are the energy mix, carbonization index and energy intensity. The applied LMDI analysis allows us to describe CO2 emissions through the disaggregated decomposition of factors and the participation of fossil fuels in each sector under study.